Naming People : Lexical Expression of Demographic Categories in Written Standard British English - Viljamaa, Kaisla (My University, 2023)
The 20th century has seen multiple social movements agitating for various rights; many taking the position that language creates social realities and therefore also agitating for language change. For example, this means focusing on the terminology used about people, either as individuals or groups. This work sets out to survey two samples of Standard British English, to see if the vocabulary in the samples has changed with respect to the demographic terminology used. The research corpus consists of two sets of editorials extracted from The Times, both spanning the months of March and April, from the years of 1976 and 2009. The total number of editorials was 272, with the entire corpus containing approximately 169 113 words. The study employed quantitative methods. Instead of focusing on changes in individual terms, most of the study focused on the demographic categories individual terms represented. This allowed the tracking of larger trends among categories of expressions. The demographic categories found in the corpus were sex, nationality, nationhood expressions, ethnicity, geographical origin, religion, race, and a selection of unclassifiable terms. After categorisation, the extracted terms were counted and the numbers from the two samples were compared. The study showed clear shifts in demographic terminology between the samples. Within the sex category terminology shifted away from androcentric generics and towards neutral forms. Among the other categories the terminology shifted towards nationality, religion and ethnicity, and away from the other demographic categories. Further research on larger corpora, or corpora across larger time spans, would also show changes for individual expressions and how long this process has been present.
Keywords: demographic terminology, standard British English, editorials, language change, sociolinguistics, race, sex, nationality, religion, ethnicity